The World Bank's support to higher education reform in Egypt: Educator's perspective on its impact for quality and equality - Rasmy, Merhan Mohamed (AUC Knowledge Fountain, 2018)
The purpose of this qualitative study is to examine and explore why despite the implementation of many reforms in Egypt’s higher education system in the past decade, problems persist in quality and impact. This is despite the closure of the World Bank supported Higher Education Enhancement Project (HEEP) in 2008. Thus, the paper aims to provide an understanding, analyze, and to evaluate the Bank’s HEEP reform that was implemented in Egypt. In the second section, I present the theoretical perspective which I believe may explain the true nature behind Egypt’s long-term relationship with international organisations, including the World Bank. This perspective is the International Education Development Framework, which covers several theories in accordance to the array of Western literature written by renowned scholars. This has led the author to question the Educators perspective in Egypt regarding the former HEEP project. The methods used consisted of I) Document and Policy Analysis of official reports and documents pertaining to the HEEP project, to obtain the perspectives of both the World Bank and the Egyptian Government (or “Borrower”) and II) Individual Interviews, to obtain the perspective of the expert educators in Egypt. The Interviews were conducted with eleven Egyptian educator experts, who were selected using the purposeful sampling, in addition to snow ball sampling. Semi-structured interviews were used. Data was collected over a period of approximately two months. The findings for the point of view of the World Bank regarding the outcome/impact of HEEP was rated as “moderately satisfactory”, while the “Borrower’s” (Egyptian Government) rated the project from their point of view, as “highly satisfactory”. It is worthy of noting that no group of stakeholders were held accountable or took any responsibility, for any hindrances of the project. In addition, several discrepancies were found as a result of the policy analysis, between the project cycle of the World Bank in relation to the actual cycle that was executed for the HEEP project. The interviews were transcribed and analysis was done using the thematic approach. Findings of the field work suggest that most of the experts perceived the HEEP project to have had limited success in achieving quality. The experts blamed the Egyptian Government for the hindrance of the project. The policy recommendations that were offered by the experts for future World Bank supported projects, were various and diverse in nature. Finally, this analysis has made the author question and request more extensive research to be conducted to explain why Egypt has maintained a long-term “partnership” with The World Bank.